On Artemisinin, Cyclopamine, D-Isocitric acid, Hyperforin, Epigenetics, Sialic Acid, and More - Giannis, Athanassios; Mousavizadeh, Farnoush (Synlett, 2019)
In this Account we present the total syntheses of artemisinin (an important antimalarial agent) and cyclopamine (the first natural inhibitor of the hedgehog signaling pathway). Furthermore, we describe the design and development of a γ-butyrolactone as an inhibitor of Gcn5 (a histone N-acetyltransferase), discuss the discovery of hyperforin and guttiferon G as the first natural products acting as inhibitors of sirtuins, and present the design of inhibitors of sialic acid biosynthesis. The biomedical background and importance are also discussed. Finally, we present the discovery and development of methods for transesterification, IBX-mediated oxidations, reduction of several functional groups with LiBH4/Me3SiCl, as well as a process enabling the synthesis of kilogram amounts of D-isocitric acid and its transformation to valuable chiral derivatives.1 Artemisinin and Malaria2 Cyclopamine and Cyclops3 Sunflowers, Krebs Cycle, and Isocitric acid4 Histones and N-Acetyltransferase Gcn55 St. John’s Wort, Hippocrates, and Sirtuins6 Sialic Acid and Inhibitors of Its Biosynthesis7 Transesterification8 IBX Reloaded9 And Finally: A Small Mistake with a Big Impact10 Epilogue
Keywords: artemisinin; cyclopamine; D-isocitric acid; hyperforin; epigenetics; sialic acid; transesterification; IBX